A history of narrative film - Cook, David A. 4 0 16; 5 (New York : Norton, 1981)
A comprehensive world film history which describes how technology, artistry, business, and politics have combined to shape the history of this medium.
Includes index.
Bibliography: p. 671-692.
Keywords: 2 -- 0; 6; History. -- Motion pictures -- 20; 20; 2